Report of second meeting between the Spanish Medical Aid Committee and officials of the Trades Union Congress and Labour Party, to discuss the proposal to send a Medical Unit to Spain, held at Transport House, on August 19th, 1936, at 3.30
1936-08-20 041-0002-004 292/946/41/2(iv)